A Physician-Based Architecture for the Construction and Use of Statistical Models - Lehmann, H. P.; Shachter, R. D. (Methods of Information in Medicine, 1994)
Physicians need specially tailored computer tools to take advantage of published research results. We present a knowledge-based computer framework -the physician-based (PB) architecture - for constructing such tools, and we use the problem of physicians’ interpretation of two-arm parallel randomized clinical trials (TAPRCT) as a working example. Statistical models are represented by influence diagrams. The interpretation of influence-diagram elements are mapped into users’ language in a domain-specific, physician-based user interface, called a patient-flow diagram. Statistical-model transformations that maintain the semantic relationships of the model and that embody clinical-epidemiological knowledge are encoded in a mediating structure called the cohort-state diagram. The algorithm that coordinates the interactions among the knowledge representations uses modular actions called construction steps. This architecture has been implemented in a Bayesian system, called THOMAS, that supports physician decision making in light of TAPRCT data. This support entails assessing clinical significance, prior beliefs, and methodological concerns. We suggest that the PB architecture applies to a wide range of statistical tools and users.
Keywords: Computer-aided Therapy; Knowledge Representation; Statistical Programs; Probability Theory; Clinical Epidemiology